Microleakage of dual-cured adhesive systems in class v composite resin restorations. - S Kasraie; M Azarsina; Z Khamverdi; F Shokraneh (Tehran University of Medical Sciences, 2012)
Microleakage is a major factor affecting longevity of composite restorations. This study evaluated the effect of polymerization mode of bonding agent on microleakage of composite restorations.Forty-eight Class V cavities were prepared on buccal and lingual surfaces of 24 extracted human premolars. Occlusal and gingival margins were placed in the enamel and dentin, respectively. Teeth were divided into four groups as follows: Group I: Optibond Solo Plus (light-cured); Group II: Optibond Solo Plus (dual-cured); Group III: Prime & Bond NT (light-cured), Group IV: Prime & Bond NT (dual-cured). Teeth were restored using Z250 composite in three increments. After polishing the restorations, samples were thermocycled for 1000 cycles and stored in distilled water for 3 months. Then they were placed in 2% fuchsine solution for 48 hours. The samples were sectioned longitudinally and evaluated for microleakage under a stereomicroscope at ×40 magnification. Dye penetration was scored on a 0-3 ordinal scale. Data were analyzed using Kruskal-Wallis, Bonferroni and Wilcoxon signed ranks test.Microleakage was significantly lower in enamel margins compared to dentin margins (P0.05). Prime & Bond NT had less microleakage compared to Optibond SoloPlus, but the difference was not significant (P>0.05).There was no difference in the amount of microleakage in Class V composite restorations using light-cured and dual-cured bonding systems. Dentinal margins of restorations exhibited more microleakage than enamel margins.